Soil conservation practices in a watershed in Southern Brazil - TELLES,TIAGO S. (2019)
Abstract: The aim of this study was to determine how often rural farmers in a watershed use no-tillage systems combined with crop rotation, contour farming and agricultural terraces. The study area was Paraná Watershed III (PB3) in the western region of Paraná State, and data from the 2006 Agricultural Census of the Brazilian Institute of Geography and Statistics were used. A frequency distribution analysis of farms as a function of the no-tillage (NT) area was conducted in combination with a cluster analysis of soil and water conservation practices (adoption of crop rotation, contour farming and agricultural terrace practices). The results showed that the farms in PB3 adopt adequate soil and water conservation practices, with 73% adopting NT combined with at least 2 other conservation practices; however, agricultural terracing was found to be the most neglected practice in the region. In addition, based on the soil and water conservation practices in the watershed, 5 groups of farms were identified, the worst of which, those located in the municipalities that mainly neglect conservation practices, live in areas with highly erodible soils.